Oracle9i development by example - Hotka, Dan (By Example Ser., 2002)
Learn the ins and outs of the Oracle9i development environment from product installation to advanced management configuration. Oracle 9i Development by Example provides coverage of everything from building, monitoring, and tuning an Oracle9i database to building forms and reports using developer 6i to understanding newer tools such as Log Miner in an easy to learn format.